Assessing Social Determinants of Health in a Prenatal and Perinatal Cultural Intervention for American Indians and Alaska Natives - Rosalina James (MDPI AG, 2021)
American Indians and Alaska Natives (AIANs) refer to cultural traditions and values to guide resilient and strength-based practices to address maternal and infant health disparities. Methods: A case study of a culturally-based educational intervention on AIAN maternal and child health. Results: Cultural teachings have successfully been applied in AIAN behavioral interventions using talking circles and cradleboards, but maternal and child health interventions are not well-represented in peer-reviewed literature. Zero publications included interventions centered around cradleboards and safe sleep. Discussion: There is a need for rigorous published research on culturally based interventions and effectiveness on health outcomes for mothers and babies. Conclusions: This paper discusses how a cradleboard educational intervention incorporates national guidelines to address maternal and infant health while mediating social determinants of health.